PENGARUH LIKUIDITAS, SOLVABILITAS DAN PERPUTARAN PERSEDIAAN TERHADAP RETURN ON ASSET PADA PERUSAHAAN RETAIL TRADE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016 - Cuaca, Deedy; Djabir, Muhammad; Jamaluddin, Jamaluddin (Aksara Public, 2018)
This research aims to know the influence of liquidity, solvency and inventory turnover to return on asset of retail trade company listed on the Indonesia Stock Exchange Period 2013-2016. The population of this research is the retail trade companies listed on the Indonesia Stock Exchange period 2013-2016. Based on the selection of the sample there are 9 company that examined for 4 years with 36 samples. The results indicate the presence of element such as liquidity, solvency, and inventory turnover simultaneously that affect the Return on assets. Showed partial liquidity, solvency and inventory turnover variable that can be explained by the adjusted R2 value of 69,7% while the rest 30,3% influenced by other variable which is not explained by this research model. The results of regression analysis obtained in this research was Y = 0.125 + 0.010X1 – 0.157X2 + 0.001X3, meaning that the liquidity and inventory turnover activity variables has a positive influence on the return on assets, but solvency variable has a negative influence on the return on assets. F test results obtained Fcount > Ftable (27.783 > 2.90), meaning that there is significant influence between liquidty, solvency, and inventory turnover activity simultaneously.